The Roles of Phytoalexin as Responsive Factors in Plant Disease Resistance and Its Benefit on Human Health - Omeiza, Mamman Muazu; Joshua.O; Abdulkadir. A. O; Mujammed. H. O; Mubarak. S. O (RADINKA JAYA UTAMA PUBLISHER, 2025)
The global challenge of food quality and safety urgently needed reform for safe consumption is closely linked to food insecurity and much emphasis is needed by farmers and plant scientists to understand the roles of phytoalexins and other natural products in the protection of economically important plants against pathogenic attacks.Despite limited experimental evidences and findings it has been suggested that phytoalexins plays major roles in disease resistance as some form of natural products which serves as antimicrobial metabolites of low molecular weight secretion which inhibit the growth of fungi pathogens while some are toxic to bacteria, nematodes and other organisms. This review provides an overview of the roles of phytoalexins a compound in plant defense and their diversity in selected plants families exploring the structural forms of its various groups as well as modes of accumulation from remote precursors through de novo synthesis of enzymes and complex defence mechanisms involving the actions of biotic and abiotic elicitors.. This article further highlight their biosynthesis and mechanisms of action delving into the distinctive metabolic pathways involved in the formation of novel synthetic phytoalexin models, mediated by enzymatic reactions and elicitor influences, shedding light on the complex interactions underlying plant defense strategies. Conclusion is drawn to emphasizes the potential of modern molecular tools in the elucidation of the mechanisms of phytoalexin synthesis and its accumulation,through the manipulation of gene(s) directly involved in their biosynthetic pathways.to produce the compounds for human therapeutic treatment for the promotion of human health.